Preliminary Results of Air Pollution Status in Selected Roadsides in Jalingo, Taraba State Nigeria - Maxwell Obia Kanu; Terkaa Victor Targema; Gideon Maumee Abednego (Indonesian Journal of Environmental Management and Sustainability, 2021)
The rapid increase in vehicular activities in the past two centuries contributes vastly to air pollution levels. In as much as Social interactions and economic growth are well enhanced by vehicular transportation in many developing countries, it is unfortunate that exhausts from vehicles contribute immensely to ambient air quality especially in the urban areas. The concentrations of carbon monoxides (CO) and carbon dioxide (CO2) emissions in selected roadsides in Jalingo have been assessed. Four roads were used as sample locations where the concentration of CO2 and CO were measured using an air quality meter for four weeks. The mean concentration of CO2 and CO obtained were respectively as follows: 542.25 ppm and 7.49 ppm for the roadblock, 540.05 ppm and 5.55 ppm for Hammaruwa way, 598.81 ppm and 17.42 ppm for market road, and 463.80 ppm and 1.08 ppm for Nigerian Labour Congress (NLC) road (control). Based on the acceptable limit of CO2 (600 ppm), the Roadblock road, Hammaruwa way, and the NLC/control road are safe. Only the market road had value that exceeded the acceptable limit, and it may be attributed to high vehicular activities on the roadsides. Therefore, more alternative roads should be constructed in other to minimize traffic congestion and also, the use of nose masks should be encouraged. For the CO, all the sites are safe because they fall within the acceptable level of CO (1-70 ppm).